Synthesis and Characterization of Porous Poly(GM-co-EGD) as a Support Matrix for Lipase Immobilization - Erwanto, Erwanto (Hydrogen: Jurnal Kependidikan Kimia, 2025)
The immobilization of lipase onto solid supports has gained significant attention as a strategy to enhance enzyme performance, operational stability, and reusability in various industrial applications. In this study, a porous methacrylate-based copolymer composed of glycidyl methacrylate (GM) and ethylene glycol dimethacrylate (EGD) was synthesized using a free-radical polymerization method. A ternary porogenic solvent system consisting of 1,4-butanediol, 1-propanol, and water (4:7:1, v/v) was employed to induce phase separation and promote pore formation within the polymer matrix. The resulting poly(GM-co-EGD) polymer exhibited an opaque white appearance with a visibly porous texture, which contrasted with the dense, transparent morphology of the non-porous polymer synthesized without porogen. FTIR analysis confirmed the presence of characteristic functional groups such as ester carbonyl (C=O), ether (Câ€“Oâ€“C), and epoxide (Câ€“O) in the polymer structure. After immobilization, significant spectral changes were observed, including the reduction in epoxide-related absorption bands (at 910 and 840 cmâ»Â¹) and the appearance of new peaks in the amide region (1640â€“1660 cmâ»Â¹), indicating successful covalent bonding between the enzyme and the polymer support. These results demonstrate that the use of a ternary porogen system effectively enhances the porosity and functional reactivity of the polymer, making it a suitable matrix for enzyme immobilization. The synthesized poly(GM-co-EGD) shows great potential as a functional support for lipase.